2005
DOI: 10.1016/j.ymthe.2005.04.017
|View full text |Cite
|
Sign up to set email alerts
|

Localized Gene Expression Following Administration of Adeno-associated Viral Vectors via Pancreatic Ducts

Abstract: Gene transfer into pancreatic cells in vivo could be of immense therapeutic benefit in cases of type 1 diabetes (T1D) through the production of molecules capable of interrupting the progression of autoimmunity or promoting regeneration of insulin-secreting beta cells. We adapted a clinically relevant surgical technique (endoscopic retrograde cholangiopancreatography) to deliver rAAV encoding human alpha1-antitrypsin (approved gene symbol SERPINA1) to the pancreas of 3-week-old Fisher 344 rats and C57BL/6 mice.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
25
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 28 publications
2
25
0
Order By: Relevance
“…A major advance is the discovery of novel AAV serotypes that possess specific structural and functional features, contributing to their differential tissue tropism, transduction efficiency and immune responses [11]. Previous studies revealed that AAV1 and AAV6 are the most efficient vector for infecting islet cells in vitro [17,21], while depending on the routes of administration (intravenous, intraperitoneal, intraductal), various serotypes showed different efficiency in transducing pancreatic islets in vivo [20,21]. We confirmed the superior efficiency of AAV8, and thoroughly studied the gene expression pattern following direct pancreatic injection, a delivery route that was not fully explored in a previous report [19].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A major advance is the discovery of novel AAV serotypes that possess specific structural and functional features, contributing to their differential tissue tropism, transduction efficiency and immune responses [11]. Previous studies revealed that AAV1 and AAV6 are the most efficient vector for infecting islet cells in vitro [17,21], while depending on the routes of administration (intravenous, intraperitoneal, intraductal), various serotypes showed different efficiency in transducing pancreatic islets in vivo [20,21]. We confirmed the superior efficiency of AAV8, and thoroughly studied the gene expression pattern following direct pancreatic injection, a delivery route that was not fully explored in a previous report [19].…”
Section: Discussionmentioning
confidence: 99%
“…However, previous studies using AAV in pancreas were mainly focused on ex vivo approaches to modify pancreatic islets for transplantation [15][16][17][18]. Not until recently were AAV vectors tested in vivo, which showed promising efficiency in transducing pancreas [19][20][21]. Nevertheless, these reports primarily focused on infection of endocrine islet cells for the purpose of treating diabetes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Receptor-specific ligands have been inserted into specific regions of the capsid gene so that they are then displayed on the surface of the capsid (Wu et al, 2000;Nicklin and Baker, 2002;Loiler et al, 2003Loiler et al, , 2005Nicklin et al, 2003;White et al, 2004;Work et al, 2004). Work is also progressing with rAAV vectors that are based on newly available serotypes and genomic variants of AAV (Chao et al, 2000;Gao et al, 2002;Rabinowitz et al, 2002).…”
Section: Attempts To Improve Vector Designmentioning
confidence: 99%
“…Although limited, recent studies are beginning to confirm the utility of direct intrapancreatic vector administration for diabetes therapy, originally reported a decade ago (32) and improved more recently (33)(34)(35). Along these lines, a recent study by Bosch and colleagues (36) is important in two respects.…”
mentioning
confidence: 99%